An Intimate Relationship between Thyroid Hormone and Skin: Regulation of Gene Expression - Antonini, Dario; Sibilio, Annarita; Dentice, Monica; Missero, Caterina (Frontiers in Endocrinology, 2013)
Skin is the largest organ of the human body and plays a key role in protecting the individual from external insults. The barrier function of the skin is performed primarily by the epidermis, a self-renewing stratified squamous epithelium composed of cells that undergo a well-characterized and finely tuned process of terminal differentiation. By binding to their receptors thyroid hormones (TH) regulate epidermal cell proliferation, differentiation and homeostasis. Thyroid dysfunction has multiple classical manifestations at skin level. Several TH-responsive genes, as well as genes critical for TH metabolism and action, are expressed at epidermal level. The role of TH in skin is still controversial, although it is generally recognized that TH signaling is central for skin physiology and homeostasis. Here we review the data on the epidermis and its function in relation to TH metabolism and regulation of gene expression. An understanding of the cellular and molecular basis of TH action in epidermal cells may lead to the identification of putative therapeutical targets for treatment of skin disorders.